Highly Sensitive and Cost‐Effective Polymeric‐Sulfur‐Based Mid‐Wavelength Infrared Linear Polarizers with Tailored Fabry–Pérot Resonance. Issue 7 (19th December 2022) - Cho, Woongbi; Hwang, Jehwan; Lee, Sang Yeon; Park, Jaeseo; Han, Nara; Lee, Chi Hwan; Kang, Sang‐Woo; Urbas, Augustine; Kim, Jun Oh; Ku, Zahyun; Wie, Jeong Jae
Abstract: Inverse‐vulcanized polymeric sulfur has received considerable attention for application in waste‐based infrared (IR) polarizers with high polarization sensitivities, owing to its high transmittance in the IR region and thermal processability. However, there have been few reports on highly sensitive polymeric sulfur‐based polarizers by replication of pre‐simulated dimensions to achieve a high transmission of the transverse magnetic field (TTM ) and extinction ratio (ER). Herein, a 400‐nanometer‐pitch mid‐wavelength infrared bilayer linear polarizer with self‐aligned metal gratings is introduced on polymeric sulfur gratings integrated with a spacer layer (SM‐polarizer). The dimensions of the SM‐polarizer can be closely replicated using pre‐simulated dimensions via a systematic investigation of thermal nanoimprinting conditions. Spacer thickness is tailored from 40 to 5100 nm by adjusting the concentration of polymeric sulfur solution during spin‐coating. A tailored spacer thickness can maximize TTM in the broadband MWIR region by satisfying Fabry–Pérot resonance. The SM‐polarizer yields TTM of 0.65, 0.59, and 0.43 and ER of 3.12 × 10 3, 5.19 × 10 3, and 5.81 × 10 3 at 4 µm for spacer thicknesses of 90, 338, and 572 nm, respectively. This demonstration of a highly sensitive and cost‐effective SM‐polarizer opens up exciting avenues for infrared polarimetric imaging and for applications in polarization manipulation. Abstract : Inverse‐vulcanized polymeric sulfur can replace expensive commercial semiconductors and chalcogenides for mid‐wavelength infrared applications. Here, a highly sensitive and cost‐effective polymeric‐sulfur‐based bilayer wire‐grid linear polarizer with a pitch of 400 nm is successfully demonstrated by systematically investigated thermal nanoimprinting conditions and precisely changed spacer thickness to control Fabry‐Pérot resonance.